PENGELOLAAN BANGUNAN CAGAR BUDAYA DI KOTA BANDUNG - Aos Kuswandi; M. Harun Al Rasyid; Siti Nurani; Zulfanida Nurul Sadiyyah (Governance, 2024)
This research aims to describe and analyze the implementation of heritage building area protection policies by the Bandung City Government. The background for conducting this research is the phenomenon of changing the function of buildings, changing the shape of buildings and even tearing down historic buildings for other functions or forms that are not like the original. Even though the Bandung City Regional Regulation policy No. 7 of 2018 concerning Management of Cultural Heritage has regulated one of the points related to the protection of heritage buildings which have high historical and architectural value of artistic value. Qualitative research methods were used in this study with data collection techniques through observation techniques, in-depth interviews and documentation studies. Observations were made in several areas where there are heritage buildings and to explore the evidence. Then interviews were conducted with elements of the Bandung City Regional Work Unit, in this case the cultural field at the Bandung City Culture and Tourism Office. Documentation studies were carried out through various documents in the form of notes, photographs and other documents related to heritage buildings and their protection policies from the Bandung City Government. The analysis is carried out in depth by describing it accompanied by scientific arguments supported by relevant concepts and theories. The results of the study concluded that the Government of Bandung City has implemented a policy to protect heritage buildings as cultural heritage. The constraints faced are the limited financial capacity of the community and the budget from the Bandung City Government for the maintenance, care and protection of cultural heritage buildings. Various efforts have been made to protect cultural heritage by continuing to increase the commitment of the Bandung City Government and collaborating with stakeholders.